Cutting room. - United States. Army. Signal Corps (photographer):::Creator::::::::::::; Flaherty, John Melvin (collector):::Contributor::::::::::::
Photograph shows a meat cutting room at Turlock, California Assembly Center. One of the evacuees is using a hacksaw while the other one is using a butcher knife to cut the beef.